A Postharvest Fruit Rot Caused by Alternaria sp. on Imported Plum Tomatoes in South Florida - Zelalem Mersha; Shouan Zhang; Jerry A. Bartz (EDIS)
Florida’s deep-water ports are ideal for importing many fruits and vegetables, including tomatoes, by ship from the Caribbean as well as Central and South American production areas. These imports are often strictly regulated for pests, but some pathogens still escape quarantine. This 3-page fact sheet describes a postharvest problem on plum tomatoes that were imported from Mexico through South Florida in 2010. Alternaria sp. was isolated from lesions on diseased fruits, pathogenicity tests were conducted on healthy fruits, and symptoms identical to the originally submitted samples were developed. Written by Zelalem Mersha, Shouan Zhang, and Jerry A. Bartz, and published by the UF Department of Plant Pathology, January 2013.